Census in Nigeria: The Processes,Politicization and Implications from Coloniality to Post-Coloniality (British Journal of Multidisciplinary and Advanced Studies, 2025)
The importance of census undertakings since independence paled into insignificance as a result of the wrangling that pervaded the activities of the disparate agglomerating ethnic units in Nigeria. This was in addition to government’s unpreparedness that was exacerbated by low capital and human capacity deficits. Yet, census was relevant since it provided the benchmark for the generation of social, economic and political data that, in turn, made for effective and efficient planning and programming. This paper examined census undertakings nexus how effectively and successfully Nigeria’s National Population Commission (NPC) conducted headcounts in the country; the problems encountered; and the often non-compliance by ethnic and dissident groups in not allowing their members participate in them. It assessed the implications of these problems vis-à-vis economic planning, growth and development. The paper concluded that the inability of the NPC to conduct censuses and the often non-compliance of ethnic groups, militants and secessionists, affected Nigeria’s overall growth and development. Primary and secondary sources were used in writing this paper while internet sources served complementary and subsidiary purposes.